Pengembangan E-Modul Berbasis Inkuiri Terbimbing Guna Meningkatkan Keterampilan Berpikir Kritis Siswa dalam Pembelajaran Ekosistem di Tingkat SMA (International Forum of Researchers and Lecturers, 2025)
This study aims to develop an inquiry-based e-module as a teaching material for ecosystem topics for tenth-grade high school students. The e-module is designed to enhance student engagement in learning and foster critical thinking skills. The research method employed is Research and Development (R&D) using Sugiyono’s development model. Validation was conducted by subject matter experts, language experts, and media experts, yielding results of 86%, 93.33%, and 94.54%, respectively, all categorized as highly feasible. Practicality tests by teachers resulted in a score of 93.75%, while student practicality surveys reached 95.4%, indicating that the e-module is highly suitable for learning. The critical thinking skills test showed an overall student score average of 77.25%, classified as high. This e-module offers several advantages, including ease of access, an engaging design, and interactive content incorporating text, images, videos, and exercises. However, challenges in its implementation include limited technological access in some schools. Overall, the inquiry-based e-module is considered effective and ready for use as an alternative teaching material for ecosystem learning in high schools.